Life cycle assessment of integrated wastewater treatment systems with constructed wetlands in rural areas. (1st April 2017) - Lutterbeck, Carlos A.; Kist, Lourdes T.; Lopez, Diosnel R.; Zerwes, Filipe V.; Machado, Ênio L.
Abstract: Studies identifying treatment technologies that combine low costs, high efficiencies, and lower environmental impacts are of great value. Thus, the present study investigated the performance of a wastewater treatment system located on a rural property by life cycle assessment. The system consisted of an anaerobic unit (upflow anaerobic sludge blanket combined with an anaerobic filter), four subsurface flow constructed wetlands, and two photoreactors. The reductions in chemical oxygen demand varied between 93% and 97%, whereas the biochemical oxygen demand decreased by 97–98%. Additionally, 97% of the total Kjedahl nitrogen, 100% of the ammoniacal nitrogen, and more than 90% of total phosphorus were removed from the wastewater. These data were used with reference to the life cycle inventory. The results obtained by the analysis of the endpoint H inventory network showed that 67.3% of the environmental impacts were related to the construction while 32.7% were associated to the operation of the system. The phototreament (45%) and anaerobic (36%) units were responsible for the highest environmental burdens of the constructions phase. By considering the operation of the system with a lifespan of 10 years, again the anaerobic unit accounted for most of the environmental impacts, mainly related to climate change. However, the system presents several potentialities, which might turn it, more environmental friendly and life cycle assessment showed that some of them such as energy recovery from the anaerobic unit will greatly reduce the environmental pressure indexes. Thus, the present study showed that the application of a life cycle assessment can give valuable insights for setting the best configurations for a wastewater treatment system in rural areas by identifying the most critical parameters and by the evaluation of actions which might reduce the environmental impacts.